Microfabrication of rubidium-85 vapor cell for optically pumped magnetometer applications through UV light decomposition of rubidium azide - Pereira, Hugo Martins (2025)
Neuroimaging methods have contributed to enhancing the knowledge of human brain activity. Magnetoencephalography is a general neuroimaging method that typically uses superconducting quantum interference devices as brain magnetic field sensors that require cryogenic cooling, putting practical and economical limitations. Optically pumped magnetometers are a promising alternative based on the use of atomic vapor cells, and eliminate the need for cryogenic conditions. This work focuses on the room-temperature synthesis of a rubidium-85 (85Rb) vapor, using 85Rb azide (85RbN3) and low-temperature anodic bonding for the vapor cell microfabrication. The cell cavities were filled with an Rb azide aqueous solution, which was decomposed under UV light to produce Rb vapor. Spectroscopic characterizations, including Fourier-Transform Infrared Spectroscopy (FTIR) and Raman spectroscopy, were used to analyze the quality of the Rb azide before the UV decomposition. The FTIR results proved the presence of the different functional groups of the Rb azide compound, in solid and aqueous solution. The typical vibrational modes of Rb azide were assigned in Raman spectra. Scanning electron microscopy (SEM) and optical microscopy proved the anodic bonding of silicon and borosilicate, and the presence of Rb vapor after UV decomposition. This work represents an important step towards improving the simplicity of atomic magnetometers fabrication using alkali metals for medical imaging applications.